Research on temperature rise of high current switchgear in distribution system. Issue 16 (29th November 2018) - Wang, Xiaorui; Cai, Suxiong; Peng, Zhaowei; Yu, Zhanqing; Gao, Shisen; Huang, Zerong; Guan, Yonggang; Xia, Haotian; Zeng, Rong
Abstract : With the increase of the load of the switchgear, the overheating of the switchgear is more and more serious. In this article, the authors give the primary heat sources in the electrical equipment. According to these sources, they explore the reason of why the switchgear can be overheated during operation. Then, they build a 3D model in the Comsol & Multiphysics® and analyse the temperature state of the switchgear from the simulation. They also carry out temperature test on KYN28 switchgear to summarise the laws of the temperature change of the switchgear. Finally, they propose a brief method to monitor the temperature and realise the function of temperature warning to avoid accidents caused by overheating.